Correlation Crossmatching Test with Effectiveness of Transfusion in Hemolytic Anemia Patients - Primadita, Cherylia; Julyani, Sri; Muhiddin, Rachmawati A. (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2024)
Hemolytic anemia is anemia caused by the premature destruction of red blood cells. Transfusion with hemolytic anemia is a dilemmatic indication and is still based on clinical decisions. Several studies assessed the effectiveness of transfusions in hemolytic anemia patients with incompatible crossmatching showed effectiveness. This study aimed to analyze crossmatching with transfusion effectiveness in hemolytic anemia patients.  Retrospective cohort observational study with medical record data from January 2019 to May 2022 of hemolytic anemia patients who got transfusion therapy. The variables included age, gender, hemoglobin levels before and after transfusion, crossmatching test, and transfusion effectiveness based on increased hemoglobin after transfusion 1 g/dL of 1 Pack Red Cell (PRC) unit. One hundred three (103) patients with hemolytic anemia 45 received PRC, 12 males (26.7%) and 33 females (73.3%). Ages 19 - < 45 years subjects had the most transfusions. Hemoglobin levels before and after transfusion showed significant differences (p-value =0.000) in the patients with a diagnosis of hereditary, unspecified, and autoimmune hemolytic anemias. The correlation between the effectiveness of transfusions with gender and age was not found (p=0.521, p=0.240). The correlation between crossmatching with the effectiveness of transfusion was not found (p=0.089). Hemolytic anemia patients with transfusion showed an increase in hemoglobin levels between before and after transfusion even with incompatible crossmatching. The correlation between the results of crossmatching with transfusion effectiveness in patients with hemolytic anemia was not found. Good premedication treatment can provide effective transfusion.